2015
DOI: 10.3897/zookeys.540.6713
|View full text |Cite
|
Sign up to set email alerts
|

Relevant genetic differentiation among Brazilian populations of Anastrepha fraterculus (Diptera, Tephritidae)

Abstract: We used a population genetic approach to detect the presence of genetic diversity among six populations of Anastrepha fraterculus across Brazil. To this aim, we used Simple Sequence Repeat (SSR) markers, which may capture the presence of differentiative processes across the genome in distinct populations. Spatial analyses of molecular variance were used to identify groups of populations that are both genetically and geographically homogeneous while also being maximally differentiated from each other. The spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…We found the lowest H O value at locus Tin06 (0.05-T. incompleta) and the highest value at loci Tbi02 for T. bicolor and Tgr06 for T. grandis (H E = 0.88). The number of alleles found for Tomoplagia species is consistent with those found in some other species of Tephritidae, such as Anastrepha fraterculus (7-18 alleles per locus, mean = 12.9; Manni et al 2015) and Ceratitis capitata (8-22 alleles per locus, mean = 13.6; Bonizzoni et al 2000), but exceed those found for Anastrepha suspensa (2-12 alleles per locus, mean = 6.1; Fritz and Schable 2004) and Bactrocera tau (2-9 alleles per locus, mean = 4.5; Yan et al 2015). Yan et al (2015) also found a locus with low observed heterozygosity for Bactrocera tau (H O = 0.069), as we found in T. incompleta (locus Tin06).…”
Section: Discussionsupporting
confidence: 85%
“…We found the lowest H O value at locus Tin06 (0.05-T. incompleta) and the highest value at loci Tbi02 for T. bicolor and Tgr06 for T. grandis (H E = 0.88). The number of alleles found for Tomoplagia species is consistent with those found in some other species of Tephritidae, such as Anastrepha fraterculus (7-18 alleles per locus, mean = 12.9; Manni et al 2015) and Ceratitis capitata (8-22 alleles per locus, mean = 13.6; Bonizzoni et al 2000), but exceed those found for Anastrepha suspensa (2-12 alleles per locus, mean = 6.1; Fritz and Schable 2004) and Bactrocera tau (2-9 alleles per locus, mean = 4.5; Yan et al 2015). Yan et al (2015) also found a locus with low observed heterozygosity for Bactrocera tau (H O = 0.069), as we found in T. incompleta (locus Tin06).…”
Section: Discussionsupporting
confidence: 85%
“…Although we recognize that A. fraterculus is a species complex in itself and our sampling might include representatives from some of the three cryptic species identified in Brazil ( Selivon and Perondini, 1998 ; Selivon et al, 1999 , 2005 ; Hernández-Ortiz et al, 2012 ; Hendrichs et al, 2015 ; Manni et al, 2015 ; Roriz et al, 2017 ), we failed to find genetic evidence for such lineages in our analyses. Thus, we failed to find significant departures from neutrality other than the suggested population size expansions.…”
Section: Discussionmentioning
confidence: 92%
“…fraterculus complex. These include studies on morphometrics [ 31 35 ], pre- and post-zygotic isolation [ 36 43 ] metaphase karyotypes [ 34 , 44 , 45 ], egg morphology and embryonic development [ 46 49 ], DNA markers [ 50 52 ] and pheromone profiles [ 53 56 ]. Some of the more recent studies have tried to incorporate multidisciplinary approaches for the same samples [ 32 , 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%